The politics of heredity : essays on eugenics, biomedicine, and the nature-nurture debate - Paul, Diane B., 1946- (SUNY series in philosophy and biology., 1998)
This book explores the development of hybrid corn, the history of eugenics, human genetics, the nature-nurture debate, the origins of the Marxian concept of proletarian science, the shift in the meaning of "fitness" in evolutionary theory, the practice of normal science in Nazi Germany, and the making and selling of science textbooks. While the topics are diverse, a common theme unites them - each explores links between biological science, social power, and public policy.